Principles of the application of strategic planning methods - Lisiński, Marek; Šaruckij, Mark (Journal of Business Economics and Management, 2006)
Strategic planning methods form an extensively developed and interrelated group of dozens of methods used for organisation strategy development. Research has confirmed that only a small amount of firms use strategic planning methods in practice due to different reasons. The publications on strategic planning are devoted mostly to theoretical issues or empirical characteristics of chosen sub‐problems related to this concept of management. The methodological aspects, if at all, are taken into account as marginal or of minor importance. The purpose of this article is to present the principles of strategic planning methods classification and application. The methodology used in this research is based on the taxonomy methods and particularly Ward's method. A total amount of 28 different strategic planning methods were chosen and classified in our study.First published online: 14 Oct 2010